Addressing Rare Outages in C-V2X With Time-Controlled One-Shot Resource Scheduling - Md Saifuddin; Mahdi Zaman; Yaser P. Fallah; Jayanthi Rao (IEEE Open Journal of Intelligent Transportation Systems)
Cellular Vehicle-to-Everything (C-V2X) has become one of the most anticipated technologies for vehicular safety network. In LTE C-V2X Basic Safety Messages (BSMs) are transmitted on radio resources that are allocated with a periodic resource reusability. This allocation is based on a semi persistent sensing-based scheduling scheme (SPS) algorithm. But, due to this reuse of periodic resources, the possibility of loss of consecutive packets between the same vehicle pair is significant. This study discusses different approaches proposed to solve this consecutive loss problem. Based on this investigation, this article suggests an efficient One-Shot based solution with a new control parameter, that performs superior to the state-of-the-art solution that is standardized in SAE J3161/1 which this article analyzes and shows to have limitation in case of high-density scenario.